Dmp1Cre‐directed knockdown of parathyroid hormone–related protein (PTHrP) in murine decidua is associated with a life‐long increase in bone mass, width, and strength in male progeny. (30th June 2021) - Ansari, Niloufar; Isojima, Tsuyoshi; Crimeen‐Irwin, Blessing; Poulton, Ingrid J.; McGregor, Narelle E.; Ho, Patricia W. M.; Forwood, Mark R.; Kovacs, Christopher S.; Dimitriadis, Evdokia; Gooi, Jonathan H.; Martin, T. John; Sims, Natalie A.
ABSTRACT: Parathyroid hormone–related protein (PTHrP, gene name Pthlh ) is a pleiotropic regulator of tissue homeostasis. In bone, Dmp1Cre‐ targeted PTHrP deletion in osteocytes causes osteopenia and impaired cortical strength. We report here that this outcome depends on parental genotype. In contrast to our previous report using mice bred from heterozygous (flox/wild type) Dmp1Cre.Pthlh f/w parents, adult (16‐week‐old and 26‐week‐old) flox/flox (f/f) Dmp1Cre.Pthlh f/f mice from homozygous parents ( Dmp1Cre.Pthlh f/f(hom) ) have stronger bones, with 40% more trabecular bone mass and 30% greater femoral width than controls. This greater bone size was observed in Dmp1Cre.Pthlh f/f(hom) mice as early as 12 days of age, when greater bone width was also found in male and female Dmp1Cre.Pthlh f/f(hom) mice compared to controls, but not in gene‐matched mice from heterozygous parents. This suggested a maternal influence on skeletal size prior to weaning. Although Dmp1Cre has previously been reported to cause gene recombination in mammary gland, milk PTHrP protein levels were normal. The wide‐bone phenotype was also noted in utero: Dmp1Cre.Pthlh f/f(hom) embryonic femurs were more mineralized and wider than controls. Closer examination revealed that Dmp1Cre caused PTHrP recombination in placenta, and in the maternal‐derived decidual layer that resides between the placenta and the uterus. Decidua from mothers of Dmp1Cre.Pthlh f/f(hom) mice also exhibited lower PTHrP levels by immunohistochemistry and were smaller than controls. We conclude that Dmp1Cre leads to gene recombination in decidua, and that decidual PTHrP might, through an influence on decidual cells, limit embryonic bone radial growth. This suggests a maternal‐derived developmental origin of adult bone strength. © 2021 American Society for Bone and Mineral Research (ASBMR).